(untitled) (Revista Iberoamericana de Bioética, 2023)
In the capital city of a Latin American and Caribbean country, in a health institution of great prestige, with accredited researchers, with an Ethics Committee that analyzes and approves or rejects the protocols, with numerous national and international documents, with the presence of a regulatory authority for investigations, something happened, without anyone noticing... until one person was, in a covert manner, recruited to participate and felt he didn’t want to be “a number and something else”.